A minimally destructive protocol for DNA extraction from ancient teeth - Harney, Éadaoin; Cheronet, Olivia; Fernandes, Daniel M.; Sirak, Kendra; Mah, Matthew; Bernardos, Rebecca; Adamski, Nicole; Broomandkhoshbacht, Nasreen; Callan, Kimberly; Lawson, Ann Marie; Oppenheimer, Jonas; Stewardson, Kristin; et al. (Genome Research, 2021)
Ancient DNA sampling methods—although optimized for efficient DNA extraction—are destructive, relying on drilling or cutting and powdering (parts of) bones and teeth. As the field of ancient DNA has grown, so have concerns about the impact of destructive sampling of the skeletal remains from which ancient DNA is obtained. Due to a particularly high concentration of endogenous DNA, the cementum of tooth roots is often targeted for ancient DNA sampling, but destructive sampling methods of the cementum often result in the loss of at least one entire root. Here, we present a minimally destructive method for extracting ancient DNA from dental cementum present on the surface of tooth roots. This method does not require destructive drilling or grinding, and, following extraction, the tooth remains safe to handle and suitable for most morphological studies, as well as other biochemical studies, such as radiocarbon dating. We extracted and sequenced ancient DNA from 30 teeth (and nine corresponding petrous bones) using this minimally destructive extraction method in addition to a typical tooth sampling method. We find that the minimally destructive method can provide ancient DNA that is of comparable quality to extracts produced from teeth that have undergone destructive sampling processes. Further, we find that a rigorous cleaning of the tooth surface combining diluted bleach and UV light irradiation seems sufficient to minimize external contaminants usually removed through the physical removal of a superficial layer when sampling through regular powdering methods.